TRANSITIVITY ANALYSIS OF AN EDITORIAL TEXT IN THE JAKARTA POST - Sunardi, Sunardi; Aliffudin, Muhammad (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
Abstract This study examines the use of Transitivity system within systemic functional linguistics (SFL) of an editorial text in The Jakarta Post entitled “A Clumsy ASEAN Summit”. The method used in this study is a descriptive qualitative method by employing content analysis. Meanwhile, the source of the data was gained from an online newspaper The Jakarta Post. The researcher collected the data by copying the text and then analyzing it using SFL and specifically the Transitivity System of lexicogrammar. It analyses the representation of processes, related participants, and circumstances contained in the text and finally analyses the field of discourse of the text under study. The results of this study show that there are four types of processes used in the editorial text entitled “A Clumsy ASEAN Summit”, namely material processes, mental processes, verbal processes, and relational processes. Material processes are widely used in the editorial text to describe the situation in the summit.